Safety and Immunological Efficacy of a DNA Vaccine Encoding the Androgen Receptor Ligand‐Binding Domain (AR‐LBD). Issue 7 (9th February 2017) - Olson, Brian M.; Bradley, Eric S.; Sawicki, Thomas; Zhong, Weixiong; Ranheim, Erik A.; Bloom, Jordan E.; Colluru, Viswa T.; Johnson, Laura E.; Rekoske, Brian T.; Eickhoff, Jens C.; McNeel, Douglas G.
Abstract : BACKGROUND: The androgen receptor (AR) is a key oncogenic driver of prostate cancer, and has been the primary focus of prostate cancer treatment for several decades. We have previously demonstrated that the AR is also an immunological target antigen, recognized in patients with prostate cancer, and targetable by means of vaccines in rodent models with delays in prostate tumor growth. The current study was performed to determine the safety and immunological efficacy of a GMP‐grade plasmid DNA vaccine encoding the ligand‐binding domain (LBD) of the AR, pTVG‐AR. METHODS: Groups of male mice (n = 6–10 per group) were evaluated after four or seven immunizations, using different schedules and inclusion of GM‐CSF as a vaccine adjuvant. Animals were assessed for toxicity using gross observations, pathological analysis, and analysis of serum chemistries. Animals were analyzed for evidence of vaccine‐augmented immunity by tetramer analysis. Survival studies using different immunization schedules and inclusion of GM‐CSF were conducted in an autochthonous genetically engineered mouse model. RESULTS: No significant toxicities were observed in terms of animal weights, histopathology, hematological changes, or changes in serum chemistries, although there was a trend to lower serum glucose in animals treated with the vaccine. There was specifically no evidence of toxicity in other tissues that express AR, including liver, muscle, hematopoietic, and brain. Vaccination was found to elicit AR LBD‐specific CD8+ T cells. In a subsequent study of tumor‐bearing animals, animals treated with vaccine had prolonged survival compared with control‐immunized mice. CONCLUSIONS: These studies demonstrate that, in immunocompetent mice expressing the target antigen, immunization with the pTVG‐AR vaccine was both safe and effective in eliciting AR‐specific cellular immune responses, and prolonged the survival of prostate tumor‐bearing mice. These findings support the clinical evaluation of pTVG‐AR in patients with recurrent prostate cancer. Prostate 77:812–821, 2017 . © 2017 Wiley Periodicals, Inc.